A comprehensive review on different types of fuel cell and its applications - Ramasamy, Palanisamy; Muruganantham, Balakrishnan; Rajasekaran, Stanislaus; Durai Babu, Babu; Ramkumar, Ravindran; Aparna Marthanda, Ayyalasomayajula Venugopala; Mohan, Sadees (Institute of Advanced Engineering and Science, 2024)
This review article provides an overview of various types of fuel cells that are currently being researched and developed. Fuel cells are electrochemical devices that convert chemical energy directly into electrical energy, making them a promising technology for clean and efficient energy production. The review covers the principles of operation and key characteristics of proton exchange membrane fuel cells (PEMFCs), solid oxide fuel cells (SOFCs), alkaline fuel cells (AFCs), direct methanol fuel cells (DMFCs), and microbial fuel cells (MFCs). The article also discusses the advantages and limitations of each type of fuel cell, as well as the current research and development efforts aimed at improving their performance and reducing their costs. Overall, this review provides a comprehensive understanding of the various types of fuel cells and their potential applications in the field of energy production.